Statistical Approach to Determining Trends in Regional Development and Peculiarities of Population Behavior in the Context of Modern Challenges - N. D. Kremlev (Статистика и экономика)
The purpose of the study is to determine the trends of regional development and the peculiarities of population behavior in the context of modern challenges. The relevance of the study of the specific behavior of the population of the regions is associated with the problems of reflecting economic development trends which affect the actions and deeds of people and the quality of their lives. At the same time, liberal approaches to the definition of behavioral strategies of the population do not allow to objectively reflect the peculiarities of regional development. The methodology is used from the point of view of substantiating digital meters reflecting the processes of interaction of needs, consumption, production and behavior of the population, their impact on the peculiarities and trends of regional development.Methods: Rosstat methodology, including the balance method, a method of comparative assessments of regional development trends and analysis of the degree of satisfaction of the needs of the population.Results. The peculiarities of the formation of the population behavior of the subsidized border region, which is directly related to the living conditions and the degree of satisfaction of people’s needs, are revealed. The unpredictable behavior of the population was used to assess the relationship between needs and the production of goods that affect the characteristics and well-being of people. It is established that the population of the Kurgan region is in a constant state of stress due to management miscalculations in inter-budgetary relations, the imbalance of interests of employers with employees who artificially underestimate the value of labor and knowledge of employees. All this affects the deterioration of demographic and migration behavior of the population, the quality of life of people.Conclusion. Official statistics allow us to truthfully determine the trends of regional development and the peculiarities of population behavior in the face of modern challenges. The results obtained allowed us to reveal the actual problems of the development of the subsidized region, which affect the behavioral strategies of the population. Also, when developing state measures to ensure people’s savings, maintaining a balance of interests of the population and employers with government authorities in order to reduce the negative impact of unpredictable behavior of people on the future.